The Effects of Organizational Inertia and Dynamic Capability on Firm Performance: Business Model Innovation as a Mediating Variable at Small Industry of Rendang in West Sumatera - Mira Permata Sari; Donard Games; Dessy Kurnia Sari (Dinasti International Journal of Education Management And Social Science, 2024)
This study aims to explore the knowledge management challenges faced by Rendang IKMs in the context of organizational inertia as a barrier and unordinary competencies as antecedents to achieving superior performance in the domestic and global markets. At the same time, know the role of business model innovation in relation to the performance of the IKM business. The research analyzed data from 105 IKM Rendang in West Sumatra and found that despite being in a state of stagnation or inertia, these businesses can still generate profits. However, inertia must still be minimized by innovating. Meanwhile, the unordinary capability (dynamic capability) that dominates rendang entrepreneurs is absorptive capability, indicating that while SMEs have enough knowledge to understand tastes and market conditions, they struggle to transform this knowledge into viable companies. Business model innovation plays a vital role in reducing company stagnation and enhancing dynamic capabilities in implementation. Moreover, it can mitigate the risk of innovation failure, a fear often faced by rendang entrepreneurs, and provide space for converting knowledge into effective strategies and products